1967
DOI: 10.1128/jb.94.4.804-811.1967
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Manifestations of Adrenergic Blockade inBordetella pertussis-vaccinated Mice

Abstract: The in vivo metabolic events which follow the administration of epinephrine, norepinephrine, or isoproterenol were examined in normal, Bordetella pertussisvaccinated, and a and adrenergically blocked mice. The normal hyperglycemic response to epinephrine was suppressed in all experimental groups. The pertussissensitized and ,B-blocked animals produced similar split patterns of altered response not duplicated by the a-blocking compounds. Those catecholamines that normally increase free fatty acids and lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1968
1968
1981
1981

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Epinephrine Refractory Hypoglycemia. It is known that injection of B. pertussis cells into experimental animals results in hypoglycemia and a decreased responsiveness to epinephrine as measured by a lack of elevation of blood sugar after injection of the catecholarnine (18)(19)(20). Table VI presents epinephrine in mice which had received between 0.1 and 1.0/~g of LPF and only a minimal response, compared to that found in control mice, in those which had received 0.02/~g of LPF.…”
Section: Pa Of Lpf and Leukocyte Countsmentioning
confidence: 97%
“…Epinephrine Refractory Hypoglycemia. It is known that injection of B. pertussis cells into experimental animals results in hypoglycemia and a decreased responsiveness to epinephrine as measured by a lack of elevation of blood sugar after injection of the catecholarnine (18)(19)(20). Table VI presents epinephrine in mice which had received between 0.1 and 1.0/~g of LPF and only a minimal response, compared to that found in control mice, in those which had received 0.02/~g of LPF.…”
Section: Pa Of Lpf and Leukocyte Countsmentioning
confidence: 97%
“…HSF does not seem to interfere with production of adrenal hormones but rather to prevent the normal action of epinephrine by "blocking" the f3-adrenergic receptors needed for some of the activities of epinephrine. Much support was given to this view when Fishel and co-workers showed that fl-adrenergic blocking agents mimic the effect of HSF and that HSF produces many metabolic disturbances associated with 3-adrenergic activity (58-60, 92,228,233). If HSF actually blocks the f-adrenergic receptors, this blocking effect must be long lasting, and as a result it may produce many other modifications in the animal.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there were feati duced hyperglycemia in mice which aI differ from those noted in other spi example, other investigators have repoi crease in blood glucose in Abut not 4 gically blocked rats after 3' , 5'-AMP a tion, although both groups were unres epinephrine (13). The present studic strated the ineffectiveness of the nuc mice, regardless of the type of adrenergi or pertussis-sensitization (Tables 1, 3 difficulties associated with any interpr these data, including variations in exj conditions, assignment of metabolic specific receptors, differences in permi various tissues to the nucleotide, and th nature of the hyperglycemic responm several points seem worthy of con There are a number of observations whi that, in mice and rats at least, catec induced hepatic glycogenolysis is a cc of a-receptor activation (8,22). emphasis is placed on other factors M -AMP on the tributions to hyperglycemia have been recently s-sensitized summarized (7).…”
Section: Discussionmentioning
confidence: 99%
“…Based primarily upon the failure of epinephrine to elicit the normal hyperglycemic response and the duplication of the histamine sensitivity by adrenergic blocking substances, it has been suggested that the histamine phenomenon is associated with a lesion in the autonomic nervous system (6). More specifically, it would appear that, of the two types of adrenergic receptors, the pertussis organism possesses a component which combines with the /3 type and renders them unresponsive to normal transmitter substances, such as epinephrine or norepinephrine or both (4,5,8).…”
mentioning
confidence: 99%